Lifestyles acquired during confinement by COVID-19 in childhood: a systematic review - De León Ramírez, Yeimy Mar; Hernández Dominguez, Xcaret Alexa; Arroyo-Helguera, Omar Elind (Horizonte Sanitario, 2023)
Objective: To know the scientific evidence to identify patterns of changes in lifestyles during childhood and their association with various anthropometric parameters in infants caused during confinement by COVID-19. Materials and methods: A systematic analysis was carried out following the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guide in the PubMed and Google Schoolar databases, the keywords used were diabetes mellitus tipo 2 or diabetes mellitus type II, hipertensión or hypertension, cuarentena or quarantine, covid-19, infantes or child, estilos de vida saludables or healthy lifestyles, sedentarismo or sedentarism, comportamientos alimentarios or eating behaviors. The search was carried out from April 2019 to June 2022. Results: The search yielded 221 articles, only 5 articles met the inclusion, exclusion and quality criteria, which show that the COVID-19 confinement caused changes in lifestyles. life that were mainly associated with a sedentary lifestyle during childhood. Conclusions: There is little information on the effects that COVID-19 confinement has caused on the lifestyles of infants, the existing information shows changes in pro-healthy eating habits in infants and decreased physical activity; therefore, activities aimed at guardians or responsible adults are recommended so that they can supervise feeding and improve nutrition, as well as carry out activities that encourage physical activity. Keywords: Healthy lifestyle; Quarentine; COVID-19; child; Feeding behavior